Preclinical Evaluation on the Tumor Suppression Efficiency and Combination Drug Effects of Fermented Wheat Germ Extract in Human Ovarian Carcinoma Cells. (1st March 2015) - Wang, Chia-Woei; Wang, Chien-Kai; Chang, Yu-Jia; Choong, Chen-Yen; Lin, Chi-Shian; Tai, Cheng-Jeng; Tai, Chen-Jei
Abstract : Fermented wheat germ extract (FWGE) is a nutrient supplement and a potential antitumor ingredient for developing an integrated chemotherapy with standard chemotherapeutic drugs for treating ovarian cancer patients. In this study, we evaluated the tumor suppression efficiency of FWGE in human ovarian carcinoma cells, SKOV-3 and ES-2, and found the half-maximal inhibitory concentrations (IC50 s) to be 643.76  μ g/mL and 246.11  μ g/mL after 48 h of FWGE treatment. FWGE treatment also induced programmed cell death by activating the caspase-7 cleavage in both SKOV-3 and ES-2 cells, but only caspase-3 and poly(adenosine diphosphate-ribose) polymerase cleavages were activated in SKOV-3 cells. Moreover, FWGE exhibited combination drug effects with cisplatin and docetaxel in SKOV-3 and ES-2 cells by enhancing the cytotoxicity of both drugs. In conclusion, we found that FWGE not only suppressed cell growth but also induced caspase-3-related and caspase-7-related cell death in human ovarian carcinoma cells. FWGE treatment further enhanced the cytotoxicity of cisplatin and docetaxel, suggesting that FWGE is a potential ingredient in the development of adjuvant chemotherapy with cisplatin or docetaxel for treating ovarian cancer patients.